The Fragility of Truth: Skimming through Noise and Bias in the Post-Truth Era - Gross, Eduard-Claudiu (Conatus - Journal of Philosophy, 2025)
In today’s society, where false information is widely spread and noise makes accurate information elusive, the concept of truth faces constant assault. This situation emphasizes the harm caused by disinformation and underscores the necessity for individuals to develop critical thinking skills to navigate through the sea of misleading noise. The present paper also explores the phenomenon of “post-truth,” where subjective opinions and feelings often override objective facts, significantly influencing people’s reactions. Furthermore, this investigation sheds light on the intricate relationship between information credibility and public perception by examining the decline of trust in scientific discoveries and the subsequent emergence of fact-checkers as a response to the erosion of factual information’s trustworthiness.